2020
DOI: 10.1055/s-0040-1708866
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Cyanoacrylate Glue Ablation of Primary Truncal Varicose Veins Compared to Existing Endovenous Techniques: A Systematic Review of the Literature

Abstract: Abstract Introduction One-third of adults in the United States and United Kingdom suffer from varicose veins. n-butyl-2-cyanoacrylate (NBCA) glue is a novel endovascular, nontumescent, nonthermal ablation technique for treatment of this condition. It has proved effective in multiple studies since its first use in 2013. The aim of this systematic review is to assess the efficacy of NBCA in ablating primary truncal varicose veins and eliminating reflux compared with exi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 40 publications
0
13
0
2
Order By: Relevance
“…The introduction of endovenous techniques almost 20 years ago changed the treatment of varicose veins [ 11 , 12 , 13 ]. Minimally invasive technology, such as segmental radiofrequency, hemoglobin-specific lasers, water-specific lasers, endovenous steam, and mechanochemical and cyanoacrylate ablation, has been proven to be safe and is becoming more popular than the standard surgical method (high ligation and stripping) [ 11 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of endovenous techniques almost 20 years ago changed the treatment of varicose veins [ 11 , 12 , 13 ]. Minimally invasive technology, such as segmental radiofrequency, hemoglobin-specific lasers, water-specific lasers, endovenous steam, and mechanochemical and cyanoacrylate ablation, has been proven to be safe and is becoming more popular than the standard surgical method (high ligation and stripping) [ 11 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Since the first approval of n-butyl cyanoacrylate for the treatment of truncal venous insufficiency in 2011, cyanoacrylate-mediated vein ablation was announced as a fast, painless and effective method in that indication [6][7][8][9][10][11][12][13][18][19][20]. The first two mentioned advantages result from no need for a time-consuming tumescent anesthesia.…”
Section: Discussionmentioning
confidence: 99%
“…In that case, the lack of tumescent anesthesia, although emphasized as the main benefit of cyanoacrylate-based procedures, does not prevent the presence of blood persisting in some segments of the vein after treatment. Since persisting blood will coagulate, subsequent fibrinolysis may result in recanalization, which may then be considered as the method-specific finding of treatment failure [10,18]. This assumption could be supported by the higher prevalence of recanalization in the VenaBlock group, observed even in the short-term assessment [14].…”
Section: Discussionmentioning
confidence: 99%
“…CAE is a novel endovascular NTNT ablation technique for treatment of incompetent truncal veins with n -butyl-2-cyanoacrylate (NBCA) glue[ 56 - 58 ]. Multiple studies have shown the effectiveness of CAE since its first use in 2013.…”
Section: Caementioning
confidence: 99%
“…The mean followed-up was 12.3 mo (1–36 mo). Two-year occlusion rates were 93.7, 90.9, and 91.5% for NBCA, RFA, and EVLA, respectively[ 58 ]. CAE had higher anatomic closure rates at 30 d than EVLA[ 16 ].…”
Section: Caementioning
confidence: 99%